Receipt for bullion received by A.L. Snowden from James C. Booth - Booth, James Curtis (1886)
Signed by James C. Booth (1810-1888).
Keywords: Smelting; Precious metals; Mint of the United States; Metallurgy; Booth, James Curtis, 1810-1888; United States Mint